Management in iodine defincy dairy animals - CHHABRA, SUSHMA; RADHAWA, S S; DHALIWAL, P S; JINDAL, R (The Indian Journal of Animal Sciences, 2011)
Single parenteral supplementation of iodine was done in iodine-deficient animals by subcutaneous route and its effect on plasma inorganic iodine and thyroid honnones (T3' T4) was studied. The iodine administration improved mean PII concentration significantly; revealed nonsignificant increase in T4 and T4 : T3 ratio; and a decrease in T3 levels in both cows and buffaloes.Â